Gold's overly long farewell as money - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
Today all countries have fiat money issued by a central bank. There is no obligation by a central bank to exchange its money for gold or any other good. Central banks have the monopoly to issue central bank money and have the power to create their money out of nothing. Creating such a monetary system is functional for a capitalist economy and must be regarded as a major feat of civilization, which could only be completed after around 200 years of capitalist development. This article traces the painful farewell from gold from the Classical Gold Standard in the early 19th century up to the end of the Bretton Woods system in the mid-20th century.
Keywords: E40; N20; P20; 330; money; gold standard; currency systems